Targeted delivery of doxorubicin by CSA-binding nanoparticles for choriocarcinoma treatment. (1st January 2018) - Zhang, Baozhen; Cheng, Guogang; Zheng, Mingbin; Han, Jinyu; Wang, Baobei; Li, Mengxia; Chen, Jie; Xiao, Tianxia; Zhang, Jian; Cai, Lintao; Li, Shoujun; Fan, Xiujun
Abstract: Gestational trophoblastic neoplasia (GTN) can result from the over-proliferation of trophoblasts. Treatment of choriocarcinoma, the most aggressive GTN, currently requires high doses of systemic chemotherapeutic agents, which result in indiscriminate drug distribution and severe toxicity. To overcome these disadvantages and enhance the chemotherapeutic efficacy, chondroitin sulfate A (CSA)-binding nanoparticles were developed for the targeted delivery of doxorubicin (DOX) to choriocarcinoma cells using a synthetic CSA-binding peptide (CSA-BP), derived from malarial protein, which specifically binds to the CSA exclusively expressed in the placental trophoblast. CSA-BP-conjugated nanoparticles rapidly bonded to choriocarcinoma (JEG3) cells and were efficiently internalized into the lysosomes. Moreover, CSA-BP modification significantly increased the anti-cancer activity of the DOX-loaded nanoparticles in vitro . Intravenous injections of CSA-BP-conjugated nanoparticles loaded with indocyanine green (CSA-INPs) were rapidly localized to the tumor. The CSA-targeted nanoparticles loaded with DOX (CSA-DNPs) strongly inhibited primary tumor growth and, more importantly, significantly suppressed metastasis in vivo . Collectively, our results highlight the potential of the CSA-BP-decorated nanoparticles as an alternative targeted delivery system of chemotherapeutic agents for treating choriocarcinoma and for developing new GTN therapies based on drug targeting.